(untitled) (IAHS Medical Journal, 2024)
Background: Langerhans Cell Histiocytosis (LCH) is a rare disorder characterized by the abnormal proliferation of Langerhans cells, which can affect various tissues and organs, often mimicking malignancies. It primarily affects children and can present with a wide range of symptoms, making diagnosis challenging. The etiology of LCH remains uncertain, though recent studies suggest it involves the aberrant growth of Langerhans cells triggering an immune response. Case Presentation: This was a case of an 18-month-old boy who came with fever of unknown origin in the Department of Paediatrics at BBMH who later on diagnosed as Histiocytosis. Conclusion: This case highlights the importance of considering LCH in the differential diagnosis of paediatric patients presenting with systemic symptoms such as fever, organomegaly and anaemia. Early recognition and appropriate treatment, including chemotherapy and corticosteroids are crucial for favourable outcomes. Continuous follow-up is necessary to monitor therapeutic response and manage potential complications. This report contributes to the understanding of LCH and underscores the need for further research into its etiology and treatment protocols. IAHS Medical Journal Vol 7(1), June 2024; 102-104